## When a certain tree was first planted, it was 4 feet tall and the height of the tree increased by a constant amount each

##### This topic has expert replies
Legendary Member
Posts: 2202
Joined: 07 Sep 2017
Thanked: 6 times
Followed by:4 members

### When a certain tree was first planted, it was 4 feet tall and the height of the tree increased by a constant amount each

by Vincen » Thu Apr 15, 2021 10:36 am

00:00

A

B

C

D

E

## Global Stats

When a certain tree was first planted, it was 4 feet tall and the height of the tree increased by a constant amount each year for the next 6 years. At the end of the 6th year, the tree was 1/5 taller than it was at the end of the 4th year. By how many feet did the height of the tree increase each year?

A. 3/10
B. 2/5
C. 1/2
D. 2/3
E. 6/5

Source: GMAT Paper Tests

### GMAT/MBA Expert

GMAT Instructor
Posts: 15472
Joined: 08 Dec 2008
Location: Vancouver, BC
Thanked: 5254 times
Followed by:1266 members
GMAT Score:770

### Re: When a certain tree was first planted, it was 4 feet tall and the height of the tree increased by a constant amount

by [email protected] » Fri Apr 16, 2021 5:06 am
Vincen wrote:
Thu Apr 15, 2021 10:36 am
When a certain tree was first planted, it was 4 feet tall and the height of the tree increased by a constant amount each year for the next 6 years. At the end of the 6th year, the tree was 1/5 taller than it was at the end of the 4th year. By how many feet did the height of the tree increase each year?

A. 3/10
B. 2/5
C. 1/2
D. 2/3
E. 6/5

Source: GMAT Paper Tests
Height of tree on day 0 = 4
Let d = the height increase each year
Height of tree at the end of the 1st year = 4+d
Height of tree at the end of the 2nd year = 4+d+d = 4 + 2d
Height of tree at the end of the 3rd year = 4+d+d+d = 4 + 3d
Height of tree at the end of the 4th year = 4+d+d+d+d = 4 + 4d
Height of tree at the end of the 5th year = 4+d+d+d+d+d = 4 + 5d
Height of tree at the end of the 6th year = 4+d+d+d+d+d+d = 4 + 6d

At the end of the 6th year, the tree was 1/5 taller than it was at the end of the 4th year
In other words, 6th year height = 4th year height + 1/5(4th year height)
Or we can write 4 + 6d = (4 + 4d) + 1/5(4 + 4d)
Simplify: 4 + 6d = 6/5(4 + 4d)
Multiply both sides by 5 to get: 5(4 + 6d) = 6(4 + 4d)
Expand: 20 + 30d = 24 + 24d
Simplify: 6d = 4
d = 4/6 = 2/3 = D

Cheers,
Brent

• Page 1 of 1